WHY DO DIGITAL TRANSFORMATION INITIATIVES FAIL? DIGITAL MINDSETS AS AN INVISIBLE STRATEGIC COMPONENT - Demirel, Hatice Gökçe (My University, 2024)
The question of why some organizations cannot achieve successful transformation despite having sufficient technological resources and infrastructure is multidimensional and complex. If we add to this question why some organizations cannot achieve digital innovation despite successfully implementing digital transformation into their business processes, we can conclude that an invisible element in organizations is used strategically incorrectly or erroneously. This study argues that this invisible strategic component is digital mindset and examines it in terms of leaders, employees, and the collective mindset of the organization, culture. In this conceptual research, digital leadership and culture have been taken as a domain and mindsets as a method to understand invisible components of success and/or failure. With this approach, two studies that have made significant contributions to digital mindset studies, Lankshear and Knobel's (2006) and Solberg et al. (2020), were taken as reference points and delved into. Digital mindsets have been examined in two different analyze level: business mindset and individual mindset at the organizational level. Firstly, this study examines two primary digital mindsets (Lankshear and Knobel, 2006)—Mindset 1 and Mindset 2—offering contrasting views on social relations, value creation, production, expertise, and intelligence. Secondly, it examines the digital mindsets, which Solberg et al. (2020) divided into four (Fixed/Zero-Sum, Fixed/Expandable-Sum, Growth/Zero-Sum, and Growth/Expandable-Sum), as a strategic tool that operates with two different mechanisms, from culture to employee and from employee to culture, in order to create and implement a successful digital transformation strategy in organizations. Although the literature highlights some aspects of digital leadership, digital transformation and technology selection strategy, and digital organizational culture, there is not yet sufficient knowledge to see their relationship with the digital mindset in a holistic way. Addressing this gap will provide insights into the interaction between leadership, culture, employee mindset, and digital technology strategy success, ultimately contributing to more holistic and effective digital transformation practices. This research contributes to the literature with two aspects of the model it proposes. First, it draws attention to the importance of the leader's mindset in terms of strategic horizon. Second, it provides a framework for the leader to develop different strategies, policies and practices according to the differences in the digital mindsets of the employees. It is aimed to develop a strategic perspective for the digital mindset, which is associated with different individual and organizational dimensions in the literature as an element of culture.
Keywords: Digital Transformation; Digital Leadership; Digital Transformation Strategy; Digital Organizational Culture; Digital Mindset